Analisis Strategi Pemasaran dalam Meningkatkan Volume Penjualan Rumah pada PT Bumi Arum Lestari Kendari - Jamaluddin Dahlan; Nofal Supriaddin; La Ode Almana (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
This article is the result of research on "Marketing Strategy Analysis in Increasing Home Sales Volume at PT Bumi Arum Lestari Kendari. The research method used in this study is a qualitative method based on field studies that aim to analyze marketing strategies in increasing house sales volume at PT Bumi Arum Lestari Kendari. Data collection techniques in this study using the method of observation, interviews and documentation. The interview technique used in this research is to ask questions to the authorities to obtain information about PT Bumi Arum Lestari Kendari's marketing strategy. This study uses swot analysis with a marketing strategy using the 4p namely product, price, promotion and place.